The Journal of Strength and Conditioning Research (The Journal of Strength and Conditioning Research)
Internet-Version of the Journal of Strength and Conditioning Research which is the NSCA's scientific journal. Published quarterly, it features original research that addresses optimal physical performance through applied exercise science. Research published in JSCR addresses many topics including: conditioning, sport and exercise demands, the effects of training programs on physical performance, and underlying biological basis for exercise performance.